How the African house gecko (Hemidactylus mabouia) conquered the world. Issue 8 (4th August 2021) - Agarwal, Ishan; Ceríaco, Luis M. P.; Metallinou, Margarita; Jackman, Todd R.; Bauer, Aaron M.
Abstract : Alien species are among the greatest threats to biodiversity, but the evolutionary origins of invasiveness remain obscure. We conducted the first range-wide sampling of Hemidactylus mabouia from more than 120 localities across Africa, Madagascar and the Neotropics to understand the evolutionary history of one of the most widely distributed, invasive vertebrates in the world. We used a multi-locus phylogeny, species delimitation, fossil-calibrated timetree, ancestral area reconstruction and species distribution models (SDMs) to determine how many putative species-level lineages are contained within H. mabouia, the timing and tempo of diversification, and the origins of commensality—providing insights into the evolutionary origins of invasiveness. Our analyses suggest ' H. mabouia ' originated in the Miocene in the Zambezian biogeographic region and includes as many as 20 putative species-level lineages, of which only Hemidactylus mabouia sensu stricto is invasive and widely distributed, including all Neotropical records. Zambezia is the hotspot for diversity within the group with 14 species in southeastern Zambezia. SDMs suggest that H. mabouia was able to establish in the Neotropics due to habitat suitability, and globalization and the slave trade probably allowed it to cross the Atlantic. Distribution models for the H. mabouia complex overpredict the range of the invasive H. mabouia sensu stricto —highlighting the importance of taxonomy in invasive species management.